2015
DOI: 10.1136/jech-2014-204427
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social, policy and physical venue features and social cohesion on condom use for pregnancy prevention among sex workers: a safer indoor work environment scale

Abstract: Background This study aims to: report on a newly developed ‘Safer Indoor Work Environmental Scale’ that characterizes the social, policy and physical features of indoor venues and social cohesion; and using this scale, longitudinally evaluate the association between these features on sex workers’ (SWs’) condom use for pregnancy prevention. Methods Drawing on a prospective open cohort of female SWs working in indoor venues, a newly-developed ‘Safer Indoor Work Environment Scale’ was used to build six multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 41 publications
1
35
0
2
Order By: Relevance
“…Since we were interested in understanding the independent impact of the different types of food insecurity on HIV risk, we used factor analysis to identify food insecurity types/subscales. Specifically, we used factor analysis with varimax rotation to assess the number of factors present among the items from the Radimer-Cornell Scale, using a maximum likelihood method, as in previous studies [15]. Factors were retained based on the following criteria: eigenvalues of >1; collectively accounted for 70–80 % of the variance; and preceded the elbow in a Scree plot.…”
Section: Methodsmentioning
confidence: 99%
“…Since we were interested in understanding the independent impact of the different types of food insecurity on HIV risk, we used factor analysis to identify food insecurity types/subscales. Specifically, we used factor analysis with varimax rotation to assess the number of factors present among the items from the Radimer-Cornell Scale, using a maximum likelihood method, as in previous studies [15]. Factors were retained based on the following criteria: eigenvalues of >1; collectively accounted for 70–80 % of the variance; and preceded the elbow in a Scree plot.…”
Section: Methodsmentioning
confidence: 99%
“…The Social Cohesion Scale has been previously adapted and validated with SWs in LMIC settings, [22, 31], as well as among indoor SWs by our group in Canada, where a high level of internal consistency was indicated (Cronbach α = 0.919) [32]. The level of social cohesion among study participants in Vancouver was based on a response to 12 items on a five point scale ranging from strongly agree to strongly disagree, with a score of 4 assigned to ‘strongly agree’ and 0 for ‘strongly disagree’.…”
Section: Study Variablesmentioning
confidence: 99%
“…However, this research has almost exclusively been drawn from women sex workers (Shannon et al, 2015), and limited work among clients of women sex workers (Goldenberg et al, 2011). For example, increasing evidence has identified that working in indoor venues and in-call spaces compared with street locations promotes reduced risks for violence by allowing women sex workers more control over screening prospective clients and negotiating the terms of transactions, such as fees, sexual services, and condom use (Bruckert & Hannem, 2013; Duff et al, 2015; Krüsi et al, 2012). The available literature, based on research conducted primarily in higher income settings (i.e., the United States, Australia), suggests that men sex workers working online differ substantially from their street-based counterparts in terms of their sociostructural risk profiles for violence and unsafe sex (Bimbi, 2007; Leary MCouns & Minichiello, 2007; Logan, 2010; Parsons et al, 2004); however, data on socioenvironmental risks are sparse and the lived experiences of men who buy or sell sex have gone largely undocumented.…”
Section: Introductionmentioning
confidence: 99%